A Theoretical Model of Architectural Design: Home and Well-being - Dalia Al-Tarazi; Rachel Sara; Annabel Morkporkpor Ami Dompey; Colin A. Booth (SureBuilt Series, 2026)
This paper investigates the relationship between architectural design of homes and inhabitants’ psychological well-being, which is understood to be achieved in terms of meeting human psychological needs. While existing design guidelines and policies inform housing design, they often overlook the extent to which these needs are satisfied. Despite people spending most of their time inside homes, the majority of built environment research on well-being focuses on non-residential settings, such as offices, schools, and healthcare facilities, resulting in a notable gap in the literature on well-being in residential environments. This research combines the two fields of architecture and psychology, by investigating theories of psychological needs as these are the key nutriments of psychological well-being. The research aims to develop a theoretical model of the architectural design of homes based on human needs to support and promote users’ psychological well-being. A mixed methods approach was adopted, first, a quantitative survey questionnaire was distributed (n=101) to explore if there was a link between residents’ perceptions of their homes and their psychological well-being. Secondly, a series of qualitative semi-structured interviews took place (n=13) to investigate, in-depth, the results of the survey. The results of the quantitative study demonstrated a direct link between residents’ satisfaction with their home and satisfaction with life in general. Further, the survey showed the importance of the physical structure of homes and of perceived opportunities for personalization in the overall satisfaction with a home and subsequently, well- being and life in general. The qualitative findings identified five key themes influencing the experience of homes: physical structure, embodied memories, security, transformability, and cultural preferences. The paper contributes by advancing the assessment of well-being in residential environments, linking human needs to architectural requirements for healthy homes, and proposing a theoretical model of housing design grounded in human needs to support psychological well-being. Provision of Affordable Housing Through Tunnel